Robustness, Exploitable Relations and History: Assessing Varitel Semantics as a Hybrid Theory of Representation - Nicolás Sebastián Sánchez (Crítica)
A constitutive theory of representation must address two challenges. The content determination challenge requires specifying why a particular state has a given content. The job description challenge requires spelling out the explanatory role that representational notions play in that theory. Recently, Nicholas Shea has advanced varitel semantics as a hybrid approach to representation to answer those challenges, supplementing teleosemantics with non-historical features —namely, exploitable relations and robustness. In this paper, I critically assess the hybrid theory’s answers to both challenges, arguing that their hybrid nature undermines their merits. In each case, I will show that it is hard to establish how the alleged complementariness of the hybrid account components works. I will conclude that internal problems beset Shea’s theory of representation.